Training optimum-path forest on graphics processing units - Iwashita, Adriana S. [UNESP]; Romero, Marcos V.T. [UNESP]; Baldassin, Alexandro [UNESP]; Costa, Kelton A.P. [UNESP]; Papa, João P. [UNESP] (INSTICC, 2014)
In this paper, we presented a Graphics Processing Unit (GPU)-based training algorithm for Optimum-Path Forest (OPF) classifier. The proposed approach employs the idea of a vector-matrix multiplication to speed up both traditional OPF training algorithm and a recently proposed Central Processing Unit (CPU)-based OPF training algorithm. Experiments in several public datasets have showed the efficiency of the proposed approach, which demonstrated to be up to 14 times faster for some datasets. To the best of our knowledge, this is the first GPU-based implementation for OPF training algorithm. Copyright © 2014 SCITEPRESS - Science and Technology Publications. All rights reserved.
Keywords: Graphics Processing Unit; Optimum-Path Forest